The Effectiveness of Melissa Officinalis L. versus Citalopram on Quality of Life of Menopausal Women with Sleep Disorder: A Randomized Double-Blind Clinical Trial - Shirazi, Mahboobeh; Jalalian, Mohamad Naser; Abed, Masoumeh; Ghaemi, Marjan (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective The present study aimed to assess the effect of Melissa Officinalis L. (a combination of lemon balm with fennel fruit extract) compared with citalopram and placebo on the quality of life of postmenopausal women with sleep disturbance.Methods The present study is a randomized, double-blind, placebo clinical trial among 60 postmenopausal women with sleep disturbance who were referred to a university hospital from 2017 to 2019. The participants were randomized to receive M. Officinalis L. (500 mg daily), citalopram (30 mg) or placebo once daily for 8 weeks. The Menopause-Specific Quality of Life (MENQOL) questionnaire was self-completed by each participant at baseline and after 8 weeks of the intervention and was compared between groups.Results The mean for all MENQOL domain scores were significantly improved in the M. Officinalis L. group compared with citalopram and placebo (p < 0.001). The mean ± standard deviation (SD) after 8 weeks in the M. Officinalis L., citalopram and placebo groups was 2.2 ± 0.84 versus 0.56 ± 0.58 versus 0.36 ± 0.55 in the vasomotor (p < 0.001), 1.02 ± 0.6 versus 0.28 ± 0.2 versus 0.17 ± 0.1 in the psychomotor-social (p < 0.001), 0.76 ± 0.4 versus 0.25 ± 0.1 versus 0.11 ± 0.1 in the physical and 2.3 ± 1.0 versus 0.35 ± 0.5 versus 0.41 ± 0.5 in the sexual domain, respectively.Conclusions The results revealed that M. Officinalis L. may be recommended for improving the quality of life of menopausal women with sleep disturbance.Trial registration The present study was registered by the name “Comparison of the efficacy of citalopram and compound of Asperugo procumbens and foeniculum vulgare in treatment of menopausal disorders” with the code IRCT2013072714174N1 in the Iranian Registry of Clinical Trials (IRCT).
Keywords: melissa officinalis l.; citalopram; menopause; quality of life; sleep disturbance